Comparison of knowledge, attitudes, experience, and opinions between teachers and guardians regarding the emergency contraceptive pill in Chiang Mai, Thailand - Kasara Sripichyakan (2018)
Teachers and guardians (parents or authorized persons) are expected to collaborate in educating female students about emergency contraceptive pills (ECPs) but it is unknown whether they have similar perspectives on ECPs. This study aimed to compare their knowledge, attitudes, experience, and opinions regarding ECPs. Questionnaires were distributed to 720 female teachers and guardians of eight randomly selected high schools and vocational schools in Chiang Mai, Thailand. There were significantly more teachers who knew about the existence of ECPs than guardians. More guardians reported some accurate information regarding ECPs than did teachers. More teachers than guardians believed that the use of ECPs was not morally wrong. Both teachers and guardians had similar experience with ECP use and similar agreement in teaching female adolescents about ECPs. The teachers and guardians had some different opinions on teaching barriers. It is suggested that both teachers and guardians are suited to teach female adolescents about ECPs, but they need preparation in different aspects. © 2006 The Authors Journal Compilation © 2006 Blackwell Publishing Asia Pty Ltd.